Pengaruh Literasi Keuangan, Usia, Return, Serta Pendapatan Terhadap Keputusan Investasi (Indonesian Version) - Fadhil Farizi Mursyidan; Usep Syaipudin (Akuntansi, 2023)
The purpose of this study was to examine the effect of financial literacy, age, returns, and income on people's investment decisions in the city of Bandar Lampung. This study uses multiple regression analysis. The sample consists of 112 respondents who live in the city of Bandar Lampung, have invested, and have income both from work and from parents. The results of the study show that financial literacy and returns do not have a significant effect on people's investment decisions in the city of Bandar Lampung, while age and income have a significant influence on people's investment decisions in the city of Bandar Lampung. This shows that financial literacy and returns are not a factor in making investment decisions. Investors also need mature age to be able to make wise decisions as well as sufficient income to make investment decisions.